2002
DOI: 10.1002/jcla.10035
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up of anti‐Aspergillus IgG and IgA antibodies in bone marrow transplanted patients with invasive aspergillosis

Abstract: A total of 89 patients at risk for, or with invasive aspergillosis (IA) were recruited from bone marrow transplantation (BMT) units in two Lisbon hospitals, and followed for 2(1/2) years to monitor their immune response. Of these patients, six developed probable IA, from which five died. The presence of serum IgG or IgA antibodies against seven Aspergillus recombinant antigens was assessed in patients with IA, using an enzyme-linked immunosorbent assay (ELISA). In parallel, the serum levels of galactomannan (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…Seventeen of the 20 prospective studies included patients undergoing standard chemotherapy and patients who received myeloablative chemotherapy and underwent autologous or allogeneic BMT or HSCT [12-14, 17-23, 31-36, 38], and the remaining 3 studies enrolled allogeneic BMT and HSCT recipients only [15,16,37]. Various age groups were included in the 20 prospective studies, as follows: adults (11 studies) [17][18][19][20][21][22][34][35][36][37][38], pediatric patients (1 study) [23], and both adult and pediatric patients (8 studies ) [12][13][14][15][16][31][32][33]. Nine studies provided information regarding autopsy ex- Pinel et al [14] c,e Bretagne et al [25] c,e amination [31,[33][34][35][36][37][38][39][40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen of the 20 prospective studies included patients undergoing standard chemotherapy and patients who received myeloablative chemotherapy and underwent autologous or allogeneic BMT or HSCT [12-14, 17-23, 31-36, 38], and the remaining 3 studies enrolled allogeneic BMT and HSCT recipients only [15,16,37]. Various age groups were included in the 20 prospective studies, as follows: adults (11 studies) [17][18][19][20][21][22][34][35][36][37][38], pediatric patients (1 study) [23], and both adult and pediatric patients (8 studies ) [12][13][14][15][16][31][32][33]. Nine studies provided information regarding autopsy ex- Pinel et al [14] c,e Bretagne et al [25] c,e amination [31,[33][34][35][36][37][38][39][40].…”
Section: Resultsmentioning
confidence: 99%
“…Because many studies did not include autopsy examination and because of decreasing rates of performance of autopsy [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], we evaluated survival (alive vs. dead) without taking into consideration autopsy finding or causes of death (aspergillosis vs. other), as reported by the original authors.…”
Section: Outcome Definitionsmentioning
confidence: 99%
“…Those based on the detection of antifungal antibodies have proven to be unreliable in transplant recipients receiving immunosuppressive agents (51). Instead, tests based on identifying fungal antigens or metabolites released into the circulation are potentially promising.…”
Section: Diagnosismentioning
confidence: 99%
“…However, IPA specific serologic studies may be useful in determining the prognosis of patients at risk of IPA, as Exposto and co-workers [75] found that an increase in IgG antibodies against the 94-kDa antigen predicts recovery from IPA. To date, Aspergillus serology is not available in North America [76].…”
Section: Serologic Studiesmentioning
confidence: 99%